Optimalisasi Tarif Layanan dengan Memperbaiki dan Meningkatkan Kualitas Pelayanan di Loka Litbangkes Pangandaran - Anjani, Yani (Politeknik Ganesha Medan, 2024)
In Indonesia, non-tax revenue is the second-largest source of state revenue, following tax revenue, and is expected to continue to increase in the future. To optimize non-tax revenue, tariffs are set, but using conventional However, if the tariff is set based on conventional methods, it can have a distorting effect. This study utilizes an activity-based costing system to establish service tariffs and assess quality at the Unit of Health Research and Development Pangandaran. An observational approach is employed, examining both primary and secondary data from a sample of 30 participants engaged in scientific tourism services and research collaboration. Technical terms are defined upon first use, and the language is objective, clear, and free of grammatical errors, following conventional formatting and citation guidelines. Non-probability sampling with a convenience approach was used. The data was evaluated using the activity-based costing system, servqual, and importance-performance analysis methods. The study conducted an importance-performance analysis of parameters related to cost and services with the goal of preserving the quality of service while avoiding high tariffs for users. Both rates were measured against the development efforts. The results showed that the scientific tourism rate yielded a cost of IDR5.884 and the research collaboration rate yielded a cost of IDR75.635, indicating a cost savings. Service quality attributes requiring improvement are responsiveness and assurance. Additionally, tangible elements and assurance must be aligned with tariff adjustments. This study offers valuable insights into setting non-tax state revenue tariffs in government work environments by emphasizing the quality of current services